KEGIATAN INDUSTRI DI DESA PUNGGAWUKAWU KECAMATAN BENUA KABUPATEN KONAWE SELATAN (STUDI KASUS PT. KARYA ALAM PERDANA) - Kadek Natalia; Iskandar Zainuddin Rela; Salahuddin Salahuddin (Jurusan Penyuluhan Pertanian FP UHO, 2025)
This study aims to find out industrial activities in Punggawukawu Village, Benua District, South Konawe Regency (Case Study of PT. Karya Alam Perdana). The selection of the research location was taken based on several considerations, namely Punggawukawu Village is a village closest to PT. Karya Alam Perdana and Punggawukawu Village have the potential for oil palm plants. The population in this study is 53 oil palm farmers. The sampling technique used in the study is a census method that requires the declaration of the entire population, resulting in a research sample of 53 oil palm farmers. Data was collected through survey techniques, interviews, literature reviews and documentation. The variables observed in the research on industrial activities of PT. Karya Alam Perdana consists of labor acceptance, transportation facilities, purchase of raw materials and environmental processing. The data was analyzed using a quantitative descriptive analysis method which was processed using the class interval formula. The results of the study show that industrial activities are classified as moderate. Industrial Activities of PT. Karya Alam Perdana is in the medium category because only the indicators of raw material purchases are doing well. The presence of this industry increases the selling price of palm oil for oil palm farmers. However, three indicators have not been implemented, namely the acceptance of labor which is now more selective, the lack of transportation facilities for crops and the suboptimal environmental treatment as well as the transparency of the Corporate Program Responsibility (CSR) program. The industrial activity of PT. Karya Alam Perdana needs to prioritize local labor, provide transportation for farmers, and implement Corporate Program Responsibility (CSR) transparently to improve efficiency and relationships with oil palm farmers in Punggawukawu Village Benua District South Konawe Regency.